SENSORY QUALITY AND ACCEPTABILITY OF SQUASH (CUCURBITA MAXIMA) CRACKERS AS INFLUENCED BY THE LEVELS OF SQUASH PUREE IN THE FORMULATION - Tamayo, Daisy G (Journal of Agriculture and Technology Management, 2024)
The main aim of this study was to develop a squash (Cucurbita maxima) cracker and determine its acceptability at Cebu Technological University during the Academic Year 2017-2018. This study was conducted in CTU – Tuburan Campus of selected courses with 90 respondents. This research utilized the descriptive method. The data were treated using a simple percentage, weighted mean, and hedonic points scale. The data gathered from the respondents were subjected to statistical treatment. The majority of the employees/teachers and students preferred treatment 2 (T2), which contains 1000 grams of flour with 500 grams of squash puree with fifteen or 16.67 percent of the employee/teacher respondents and thirty-four or 37.78 percent of the respondents preferred treatment 2 (T2) because it has a good sense of taste, texture, aroma, and color and more appealing. Furthermore, the positive response of the respondents/consumers and overwhelming demand for the product can be used as an input to the Income Generating Project of the Institutions. It was recommended further that the squash crackers can be used as an Income Generating project for the Institution. The food technology instructions, it could serve as an additional input to their instructions. For further development of the product, future research could conduct studies to feature more attributes that help the product more realize and become a productive one.